PERANCANGAN SISTEM INFORMASI PENGELOLAAN ARSIP PADA PT PERUSAHAAN PELAYARAN NUSANTARA PANURJWAN - Andy Kampae, Muhammad Hijjaz Yunus; Arkam, Nur (ADMIT: Jurnal Administrasi Terapan, 2024)
Archiving actions are carried out to ensure the company's continuity of operations. Archiving at an archive company provides not only as a source of information, but also as a memory center and a tool for monitoring organizational management actions. Archives are a valuable source of data for planning, analysis, development, policy formulation, decision making, reporting, accountability, assessment, and effective control. PT Perusahaan Pelayaran Nusantara Panurjwan (PPNP) does not yet have a website for digital archiving, which allows information to be retrieved more quickly and accurately. The goal objective of this study was to create an information system to assist with archive management at the research location. This study applied a qualitative approach. The data collected by the researcher, specifically the interview stage conducted in this study, seeks to get the relevant information. The following stage involves firsthand observation of activities linked to the subject under investigation. Finally, the literature study step aims to collect data, review the literature, and look for information relevant to this project. The result of this study will be used to create an archive website to help PPNP workers do their jobs more efficiently. The website that was built was successful in making it easier for archive administrators to archive all types of documents, saving time while searching archives and reducing the chance of document loss.